An Image Encryption Application of Chaotic Map based True Random Bit Generator - Ince, Esra; Karakaya, Baris; Turk, Mustafa (Institute of Electrical and Electronics Engineers Inc., 2022)
This paper presents an implementation of discrete chaotic map based true random bit generation by using two Tent maps which are driven different initial conditions. As the chaotic systems are very sensitive to initial conditions, the same Tent map circuits give different value for different initial conditions. From the start of this point of view, the proposed electronic circuits are simulated on Orcad-Pspice environment and the random bit stream is obtained from the output of comparator circuit. Obtained bit stream is tested by using NIST 800.22 statistical test suite to demonstrate the randomness of proposed system. The results of statistical tests show that the proposed random bit generation is suitable for the usage in basic encryption systems. An image encryption application is executed using obtained bit stream successfully. © 2022 IEEE.
19th IEEE International Multi-Conference on Systems, Signals and Devices, SSD 2022 -- 6 May 2022 through 10 May 2022 -- Setif -- 184720
Keywords: chaos; statistical tests; tent map; true random bit